Acoustic and visual monitoring for cetaceans along the outer Washington coast - Oleson, Erin M.; Calambokidis, John; Falcone, Erin; Schorr, Greg; Hildebrand, John A. (Monterey, California. Naval Postgraduate School, 2009)
Since July 2004, visual and acoustic monitoring efforts for marine mammals have been conducted in waters off the outer Washington coast. These efforts have been specifically to determine the seasonal occurrence of marine mammal species and to estimate their relative abundances, particularly in the area of the proposed expansion of the U.S. Navy's Quinault Underwater Tracking Range (QUTR) of the Northwest Range Complex. This has resulted in the first multi-year, year-round effort in 20 years to document and understand the presence of marine mammal species in this region. This report summarizes all data so far collected, presenting analyses of seasonal occurrence, variation in sighting distribution, and evaluation of relative abundance for all species that can be consistently identified from the visual and acoustic data sets. N0002407WX12527 CNO(N45)